MONITORING OF THE HEALING PROCESS OF ORAL MUCOSA IN THE PERIIMPLANT AREA DURING THE POSTOPERATIVE PERIOD - Slynko, Yu.O.; Sokolova, I.I.; Garmash, O.V.; Skydan, K.V. (World of Medicine and Biology, 2025)
Despite high success rates, failures still occur at various observation periods of dental implantation. Therefore, the search for criteria to predict and prevent the risk of complications in dental implantation is naturally increasing. The purpose of this study was to investigate the characteristics of the peri-implant mucosal tissues after dental implant surgery during the healing phase. A total of 67 patients aged between 25 and 45 years were placed single dental implants. Signs of inflammation in the peri-implant area recorded included pain, hyperemia, and swelling on the 3rd, 7th, 10th, 14th, and 20th day. The performed study demonstrated a dependence of the mucosal condition in the operative intervention zone on its duration and a direct impact on the postoperative discomfort period experienced by patients.
Keywords: dental implant; oral mucosa; early failure; risk factor; dentition defects; secondary adentia